2011
DOI: 10.1016/j.ultsonch.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound on the thermal and structural characteristics of proteins in reconstituted whey protein concentrate

Abstract: The sonication-induced changes in the structural and thermal properties of proteins in reconstituted whey protein concentrate (WPC) solutions were examined. Differential scanning calorimetry, UV-vis, fluorescence and circular dichroism spectroscopic techniques were used to determine the thermal properties of proteins, measure thiol groups and monitor changes to protein hydrophobicity and secondary structure, respectively. The enthalpy of denaturation decreased when WPC solutions were sonicated for up to 5 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
234
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(271 citation statements)
references
References 37 publications
34
234
3
Order By: Relevance
“…This was due to ultrasound and longer time providing more power to facilitate more high-molecular weight fragments degradation, resulting in weakening the gel network. However, there was no significant difference between WB1 and UB1, this might be because ultrasound produce protein aggregation at low temperature for short time (Chandrapala et al 2011). Protein patterns and free amino group content The molecular weight of gelatin was analyzed by SDS-PAGE (Fig.…”
Section: Melting Pointmentioning
confidence: 96%
See 2 more Smart Citations
“…This was due to ultrasound and longer time providing more power to facilitate more high-molecular weight fragments degradation, resulting in weakening the gel network. However, there was no significant difference between WB1 and UB1, this might be because ultrasound produce protein aggregation at low temperature for short time (Chandrapala et al 2011). Protein patterns and free amino group content The molecular weight of gelatin was analyzed by SDS-PAGE (Fig.…”
Section: Melting Pointmentioning
confidence: 96%
“…It was also noticed that gelatin extracted by UB showed slightly lower content of protein at the range of 70 KDa-85 KDa, for ultrasound had great effects on hydrolysis of gelatin. However, the β-chain was still observed in UB5, due to the large shear forces generated from cavitation breaking inter and intramolecular bonds, which in turn may lead to fragmentation of clusters and aggregates (Chandrapala et al 2011). Free amino groups of six samples are shown in Fig.…”
Section: Melting Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA of WPI films without nanoparticles was 40° ± 3°, decreasing slightly as the level of sonication amplitude increases. This decrease in the contact angle could be due to the restructuring of the proteins at higher sonication levels that lead to less exposure of hydrophobic regions of the protein to the surface (Chandrapala et al, 2011). WPI film swelling was observed during the contact angle measurements using a water droplet.…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…In another study, lactose yield was found to be increasing with a decrease in pH from 16% (w/v) lactose concentration without protein content and acetone as an anti-solvent (Patel and Murthy, 2009). It is reported that the use of sonication in whey protein concentrate solutions does not appear to change the protein structure to a significant degree, which can influence the functional properties of dairy systems during processing (Jayani et al, 2011). …”
Section: Effect Of Protein Concentration On Lactose Yieldmentioning
confidence: 97%